1992 - Lions Gate ([Place of publication not identified?]: Lions Gate, 2024)
In 1992, Mercer is desperately trying to rebuild his life and his relationship with his son amidst the turbulent Los Angeles uprising following the Rodney King verdict. Across town, another father and son put their own strained relationship to the test as they plot a dangerous heist to steal catalytic converters, which contain valuable platinum from the factory where Mercer works. As tensions rise and chaos erupts, both families reach their boiling points when their worlds collide. Actor(s) Tyrese Gibson, Scott Eastwood, Ray Liotta. Director(s) Ariel Vromen. Lions Gate; 031398343080; 2 Disc(s); 96 min; Thriller, Crime; R; 11/05/24
[Typographic symbols and accents removed for systems compatibility.]
Widescreen edition.
Rating: R.
DVD, color, widescreen, NTSC.
Keywords: Feature Films; Video recordings